Gab2 promotes acute myeloid leukemia growth and migration through the SHP2‐Erk‐CREB signaling pathway. Issue 4 (24th March 2022) - Gong, Rui; Li, Haoying; Liu, Yaqi; Wang, Yanyan; Ge, Lu; Shi, Liuzhi; Wu, Guang; Lyu, Jianxin; Gu, Haihua; He, Licai
Abstract: Acute myeloid leukemia (AML) is a hematologic malignant disease largely affecting older adults with poor outcomes. Lack of effective targeted treatment is a major challenge in managing the disease in the clinic. Scaffolding adaptor Gab2 is amplified in a subset of AML. However, the causative role of Gab2 in AML remains to be explored. In this study, it was found that Gab2 was expressed at high levels in AML patient samples and AML cell lines. Experiments by knocking down Gab2 expression using shRNA showed that Gab2 promoted AML cell growth and migration in vitro and in vivo. Further studies using Gab2 mutants and pharmacological inhibitors revealed that Gab2 increased CREB phosphorylation via the SHP‐2/Erk signaling pathway. CREB phosphorylation contributed to Gab2‐induced cell migration by increasing MMP2 and MMP9 expression. This research indicates that high Gab2 expression promotes AML progression through the SHP2‐Erk‐CREB signaling pathway. CREB suppression may help treat AML with high Gab2 expression. Graphical Abstract: Data to support model that Gab2 promotes AML progression through the SHP2‐Erk‐CREB pathway.